Association between 5'-UTR and 3'-UTR Polymorphisms of the TYMS Gene and Breast Cancer in Kurdish Women of Iraq - Mohamad, Kazhal Shekh (Asian Pacific journal of cancer prevention : APJCP, 2021)
Breast cancer is a common cancer found among women worldwide. Many polymorphisms can play a role in the development of this disease. The study was conducted to evaluate whether 2R/3R and 6bp insertion/deletion polymorphisms of the TYMS gene are associated with breast cancer risk in the Kurdish Iraqi population.Breast cancer is a common cancer found among women worldwide. Many polymorphisms can play a role in the development of this disease. The study was conducted to evaluate whether 2R/3R and 6bp insertion/deletion polymorphisms of the TYMS gene are associated with breast cancer risk in the Kurdish Iraqi population.DNA was extracted from EDTA-treated peripheral blood samples and included 100 patients affected by breast cancer and 100 controls. Genotyping was performed by PCR-electrophoresis.MATERIALS AND METHODSDNA was extracted from EDTA-treated peripheral blood samples and included 100 patients affected by breast cancer and 100 controls. Genotyping was performed by PCR-electrophoresis.Our results showed a significant association between 6bp deletion homozygote genotype in breast cancer patients compared to healthy individuals (P = 0.042). No significant differences were observed for other allelic and genotypic frequencies.RESULTSOur results showed a significant association between 6bp deletion homozygote genotype in breast cancer patients compared to healthy individuals (P = 0.042). No significant differences were observed for other allelic and genotypic frequencies.This study, performed for the first time on the Kurdish population, highlighted the need for further studies of the TYMS gene polymorphisms. .CONCLUSIONThis study, performed for the first time on the Kurdish population, highlighted the need for further studies of the TYMS gene polymorphisms. .